2017
DOI: 10.1016/j.cosust.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of bitcoin and blockchains

Abstract: Bitcoin is an electronic currency that has become increasingly popular since its introduction in 2008. Transactions in the bitcoin system are stored in a public transaction ledger ('the blockchain'), which is stored in a decentralized, peer-to-peer network. Bitcoin provides decentralized currency issuance and transaction clearance. The security of the blockchain depends on a compute-intensive algorithm for bitcoin mining, which prevents double spending of bitcoins and tampering with confirmed transactions. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
149
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(159 citation statements)
references
References 35 publications
0
149
0
10
Order By: Relevance
“…Further, there is a need to understand the ecological implications of powering an expanding network of compute ability required to sustain blockchains. For example, mining bitcoins requires a surprising and ever-growing amount of energy (Vranken 2017). Subsequently, we see a need to study the potential effects of the technology on the distribution of wealth, prevailing social arrangements, and geopolitical balance.…”
Section: The Future Of Blockchain In Is Researchmentioning
confidence: 99%
“…Further, there is a need to understand the ecological implications of powering an expanding network of compute ability required to sustain blockchains. For example, mining bitcoins requires a surprising and ever-growing amount of energy (Vranken 2017). Subsequently, we see a need to study the potential effects of the technology on the distribution of wealth, prevailing social arrangements, and geopolitical balance.…”
Section: The Future Of Blockchain In Is Researchmentioning
confidence: 99%
“…However, both works do not discuss about the limitations that hinder a widespread usage of the blockchain technology in the banking system. In addition, we can cite the work by Vranken [8], who focused on the estimation of the power usage of the Bitcoin network, considering four families of mining hardware. He concluded that the order of magnitude of the energy power is 100 MW.…”
Section: Introductionmentioning
confidence: 99%
“…PoW requires limited communication between replicas, can support many replicas, and can operate in unstructured geo-scale peer-to-peer networks in which independent parties can join and leave at any time [81]. Unfortunately, PoW incurs a high computational complexity on all replicas, which has raised questions about the energy consumption of Bitcoin [31,91]. Additionally, the complexity of PoW causes relative long transaction processing times (minutes to hours) and significantly limits the number of transactions a permissionless blockchain can handle: in 2017, it was reported that Bitcoin can only process 7 transactions per second, whereas Visa already processes 2000 transactions per second on average [79].…”
Section: Related Workmentioning
confidence: 99%